Morbidity and Mortality Pattern of Patients Admitted into Paediatric Intensive Care Unit of Tertiary Level Hospital of Nepal - Shrestha, Anil Kumar; Bhattarai, Susan; Paudel, Prajwal; Basel, Prem Lal (Journal of Nepal Paediatric Society, 2020)
Introduction: The paediatric intensive care unit (PICU) takes care of critically ill paediatric patients. Regular evaluation of the outcomes of patients admitted to PICU is important to assess the effectiveness of various interventions. This study aimed to find the morbidity and mortality pattern of patients admitted to PICU of tertiary level Paediatric hospital of Nepal. Methods: We conducted a retrospective, cross sectional observational study using the records of all the patients admitted to PICU of a tertiary level hospital from January 2017 to August 2017. We collected data on age, sex, geographical distribution, duration of PICU stay and the morbidity and mortality outcomes. Outcome is classified as transfer to ward, leave against medical advice (LAMA) and death. Data were analysed descriptively using SPSS version 23. Results: Out of 358 patients admitted to PICU, the mean age was 1.83 years. Majority were infants (54.5%) with male:female ratio of 1.8:1. The major causes of PICU admission were respiratory disease (27.7%) followed by CNS disease (19.6%) and infections (17.3%). The average length of stay was 6.27 days. Overall mortality was 22.7%. Conclusion: Respiratory infections were the primary cause of PICU admission and overall mortality rate was high at 22.7%. However, mortality rate was even worse for patients with multi-system involvement. We need prospective studies to examine the underlying reasons for mortality among patients with multi-system involvement.